Adsorbing behavior of polycarboxylate superplasticizer in the presence of the ester group in side chain. Issue 5 (4th May 2017) - Tan, Hongbo; Guo, Yulin; Ma, Baoguo; Li, Xin; Gu, Benqing
ABSTRACT: The effect of the ester group in side chain on adsorbing behavior and dispersion of polycarboxylate superplasticizer (PC) was studied by comparing the performance of two types of PC. The fluidity of cement paste was tested to discuss the dispersing ability and dispersing retention ability of PC. The total organic carbon analyzer was used to measure the adsorption amount, and the adsorption layer was obtained by x-ray photoelectron spectroscopy. Fourier-transform infrared spectroscopy, nuclear magnetic resonance, and pH value were used to verify the stability of the ester group, and the electrokinetic properties of cement particle were confirmed using the zeta potential measurement. The results show that the ester group in side chain reduces the initial dispersing ability while it increases the dispersing retention ability. The dispersing retention ability depends on the increase of adsorption amount and adsorption layer in 5–60 minutes, and the greater increase leads to the better dispersing retention ability. The ester group can be decomposed to release carboxyl group to enhance the adsorbing ability of PC under the condition of cement hydration, which is the main reason for the greater increase of adsorption amount and adsorption layer and the improvement in dispersing retention ability. It suggests that grafting the ester group is a good way to enhance the dispersing retention ability. GRAPHICAL ABSTRACT: